Pengaruh Metode Latihan, Bentuk Latihan Kecepatan dan Kelincahan terhadap Prestasi Lari 100 Meter - -, Rumini; KS, Soegiyanto; Lumintuarso, Ria; Rahayu, Setya (Media Ilmu Keolahragaan Indonesia, 2012)
Kesalahan yang sering terjadi pada sprinter terletak pada teknik berlari, yaitu posisi badan pelari rendah dan tubuh terlalu tegak, jangkauan panjang langkah pelari terlalu pendek. Penelitian ini bertujuan untuk mengetahui pengaruh metode latihan koordinasi dan kecepatan reaktif (quickness), pengaruh bentuk latihan kontras dan non-kontras, dan kelincahan cepat dan lambat terhadap prestasi lari 100 meter. Penelitian menggunakan desain faktorial 2x2x2. Sampel penelitian terdiri dari 58 sprinter pelajar putra usia 13-17 tahun dari kabupaten Pati dan kendal. Hasil penelitian adalah: terdapat pengaruh yang signifikan antara metode koordinasi dan kecepatan gerak reaktif, terdapat pengaruh yang signifikan antara bentuk latihan kontras dan non kontras, terdapat pengaruh yang siginifikan antara kelompok sampel kelincahan cepat dan lambat terhadap prestasi lari 100 meter. Disarankan kepada pelatih sprint, dapat mengembangkan kecepatan sprint melalui metode latihan kecepatan gerak rektif dengan bentuk latihan non-kontras.Mistake that often occur in the short-distance runners (sprinters) in particular student sprinters lie in the running technique, which are the hips tend to lean forward while running, the stride length is too short. This study aimed to determine the difference between: the effect of coordination and reactive movement speed (quickness) training methods, the contrast and non-contrast running form practice, the influence between fast and slow agility, and the interaction between training methods, form speed training, and agility on the student sprintersÃ¢â¬â¢ at 100 meters. This research is an experiment study with 2x2x2 factorial design. The research sample was consisted of 58 sprinters, aged between 13-17 years old from Kendal and Pati. The data were analyzed by Multivariate Analysis of Variane (MANOVA). The results are as follows: There is a significant difference between coordination training methods and reactive movement speed (quickness) against stride frequency, optimal stride length and average stride length, There is a significant difference between the form of contrast exercise and non-contrast exercise, There is a significant difference between fast agility and slow agility, and There is a significant interaction effect between training methods, the form of training and the agility to 100 meters. Based on these results, it is recommended to: the athletic trainers for a short length or sprint, and be able to implement the reactive speed training (quickness) and the form of non-contrast training as one of the alternative method for developing running speed (sprint).